China’s Semiconductor Industry under US Restrictions - Ke DING (East Asian Policy)
This article reviews US semiconductor export controls on China and argues that, with a second Trump administration—particularly regarding advanced process nodes and artificial intelligence (AI) chips—those restrictions will tighten even further. In response, China has ramped up investments across its entire semiconductor ecosystem, steadily enhancing self-sufficiency at every stage of the supply chain. Looking ahead, China’s global influence in the mature-process chip sector is expected to continue growing. In addition, it is likely to prioritise the development of next-generation semiconductor technologies while promoting the expansion of digital ecosystems centred on Chinese semiconductors throughout the Global South.